MANAJEMEN PESERTA DIDIK SEBAGAI UPAYA MENINGKATKAN MUTU PENDIDIKAN SEKOLAH DASAR - Wati, Erna; Shaliha, Diva Dzakyrani; Octaviana, Fadhila; Supriyadi, Supriyadi; Izzatika, Amrina (Prodi Pendidikan Guru Sekolah Dasar (PGSD) FKIP Universitas Pattimura, 2024)
Schools cannot succeed in achieving national education goals without good management, one of which is student management. This management is integrated with coaching and development activities. Therefore, schools must maximize student management in order to achieve high educational goals. This research is a qualitative library study that collects secondary data or library research. Literature sources that will be used in this research include journals, books, articles, and others. The development and coaching of students is one example of the use of this management. This can be realized by educational institutions through intracurricular and extracurricular activities designed to improve the quality of learning.